Application of Treffinger Learning Model to Improve Creative Reasoning and Mathematical Problem Solving Skills as Well as Student Learning Interests - Kusuma, Jaka Wijaya; Jefri, Ulfi; Hidayat, Ardi; Hamidah, Hamidah (Universitas Muhammadiyah Mataram, 2020)
In the learning process it is very important to try to get students to think creatively in solving problems and engaging actively. This research is an experiment in the form of design pretest postest control group design. The subjects in this study were two classes of 62 grade VIII junior high school students. The instruments used are tests of creative reasoning skills and mathematical problem solving in the form of 5 essay questions and learning interest questionnaires. Analyze data using Gain test, Chi Square test and Contingency Coefficient. The results found that improved creative reasoning skills as well as the mathematical problem-solving abilities of students with Treffinger learning were superior to regular learning. In addition, it was also found that the higher the student's learning interest the higher their creative reasoning skills and mathematical problem solving skills. Other findings include associations between students' learning interests, mathematical creative reasoning skills and students' mathematical problem-solving skills classified as moderate.